2020
DOI: 10.3390/foods9081068
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flow UV-C Irradiation Effects on the Physicochemical Properties of Aloe vera Gel and Pitaya (Stenocereus spp.) Blend

Abstract: Physicochemical properties of a blend of 10% Aloe vera gel with 5% pitaya juice subjected to UV-C doses of 16.5, 27.7, and 40 mJ/cm2 were evaluated at pH 3.5 and 5.5. Unprocessed treatments were used as the control. The a* color parameter decreased and luminosity increased at pH 3.5. The decrease in the reddish color was consistent with the decrease in total betalains content and stabilized at pH 5.5. The NMR analyses of UV-C treatments showed changes in betalains signal patterns. Polyphenolics content was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Nevertheless, UV-C irradiation has been shown in prior food research to induce availability of phytochemicals in various fruits and vegetables. Specific studies have reported increased carbohydrate content after UV-C treatment [ 27 , 28 ], and also, showed maintenance, or even, higher levels of polyphenols and antioxidant capacity [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, UV-C irradiation has been shown in prior food research to induce availability of phytochemicals in various fruits and vegetables. Specific studies have reported increased carbohydrate content after UV-C treatment [ 27 , 28 ], and also, showed maintenance, or even, higher levels of polyphenols and antioxidant capacity [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ultraviolet light, especially shortwave ultraviolet light (UV-C) is an innovative non-thermal technology for minimal food processing that not only improves food safety, enhances their appearance and nutrient content, but also extends the shelf life of food products (Cheigh et al, 2012;Koutchma et al, 2016). The advantages of UV-C comprise the absence of some toxic wastes or effects, low energy intake, low operating costs (Meléndez-Pizarro et al, 2020;Ricciardi et al, 2020). The use of UV-C leads to the minimal changes in nutritional and quality characteristics of foods, as well as microbiological safety assured by the inactivation of microbes in some liquid foods such as carambola, watermelon and pomegranate juice (Bhat et al, 2011;Zhang et al, 2011;Pala&Toklucu, 2011).…”
Section: Introductionmentioning
confidence: 99%